Co-Teaching in Secondary Schools Teacher Reports of Developments in Australian and American Classrooms / Don Rice and Naomi Zigmond. - Rice, Don (Distributed by ERIC Clearinghouse, 1999)
Co-teaching approaches to support students with disabilities in inclusive secondary classrooms were investigated through interviews with and classroom observations of 17 teachers. Data collected in Queensland (Australia) and Pennsylvania (USA) public schools allowed comparisons of teacher roles and responsibilities under two education systems. The co-teaching partnerships in both countries were dominated by subject teachers, with special educators being assigned monitoring or helping duties within the class. Teachers stressed the importance of school-wide commitment to inclusive principles for co-teaching to succeed. Professional and personal compatibility between co-teaching partners were seen as critical for success by most respondents. Barriers to the introduction of co-teaching in secondary schools were reported to be entrenched attitudes rejecting inclusion and administrators' unwillingness to commit the required time and resources. Teachers believed that well implemented co-teaching results in academic and social gains for all students and should be regarded as an effective support option for inclusive secondary classrooms. (Author/SM)